Exploring the therapeutic potential of Malaysian Stevia rebaudiana (Bertoni) Bertoni leaves essential oil: a comprehensive study on cell viability and biological effects for topical applications - Mohamad Zen, Nur Izzati; Zaidan, Uswatun Hasanah; Abd. Gani, Siti Salwa; Shamsi, Suhaili; Hassan, Masriana; Marikkar, Nazrim (Institute of Medicinal Plants, ACECR, 2024)
The abundance of plant resources in Malaysia has gained the attention of many researchers to explore more pharmacological effects of plant’s essential oil (EO). EO from Stevia rebaudiana (Bertoni) Bertoni (SrB-EO) leaves consists of a rich blend of a variety of volatile molecules and bioactive compounds which currently attract the attention of a lot of researchers due to its high potential to play a role in the therapeutic activity. In the present study, SrB-EO used was extracted using a Soxhlet extractor in absolute ethanol. The cell viability on SrB-EO has been investigated using Hs27 skin fibroblast cells against two biological assessments; anti-inflammatory and antimicrobial assays. It shows that 500 µg/mL was the highest concentration of SrB-EO which is considered non-toxic (82.08% cell viability) and demonstrates a primary significant cell proliferative effect toward cells. The maximum inhibition percentage of nitrite of SrB-EO was 33.12%, which showed a good anti-inflammatory property and SrB-EO showed an antimicrobial effect toward Gram-positive bacteria; Bacillus subtilis B29 and Staphylococcus aureus ATCC 43300. The minimal inhibition concentration (MIC) of B. subtilis and S. aureus were 6.25 mg/mL and 3.13 mg/mL of SrB-EO respectively, and the minimal bactericidal concentration (MBC) of B. subtilis and S. aureus were 12.50 mg/mL and 10.42 mg/mL of SrB-EO, respectively. This study concluded that a low concentration of SrB-EO is non-toxic toward human skin cells and these EOs possess satisfactory anti-inflammatory and antibacterial properties. Thus, SrB-EO can be used as an alternative therapeutic agent for topical application in the medicinal field.